PERANAN MAJELIS PENGAWAS DAERAH NOTARIS DALAM MENCEGAH TERJADINYA PERBUATAN MELAWAN HUKUM OLEH NOTARIS DI KOTA MEDAN - HAKIKI WARI DESKI (PREMISE LAW JURNAL, 2017)
In performing his duties, a Notary has to comply with the provisions and rules stipulated in the Laws and other regulations determined by the Association of Indonesian Notary. When a Notary makes a mistake related to his professionalism, the Court of Notary is the only authorized institution to verify and hand a decision down to him, held by a hierarchical Supervisor of Notary. The problems in this thesis are about the mechanism of Notary Supervisory run by the MPD (Regional Supervisors), what kinds of Notary’s actions can be prevented from by the MPD, and how about the role of MPD to prevent a Notary form committing actions contrary to the Notary Act. There were 3 informants in this research; namely, 2 notaries and 1 Secretary of Regional Supervisor of Medan. The mechanism of the notary supervision conducted by MPD consists of some stages. The form of violations or prohibitions for a notary pursuant to the Notary Act and the mostly recommended sentence from MPD to MPW is a written warning. The role of the Regional Supervisor of Medan to manage and supervise a notary is firstly, to implement a preventive and curative supervision by preventing the Notary from committing violation and managing the Notary; and secondly, to conduct socialization to relevant parties. Keywords: Regional Supervisor, Notary, Legal Resistance